Src/NF-κB-Targeted Anti-Inflammatory Effects of Potentilla glabra var. Mandshurica (Maxim.) Hand.-Mazz. Ethanol Extract - Kim, Haeyeop (Biomolecules, 2020)
Inflammation is a complex protective response of body tissues to harmful stimuli. Acute inflammation can progress to chronic inflammation, which can lead to severe disease. Therefore, this research focuses on the development of anti-inflammatory drugs, and natural extracts have been explored as potential agents. No study has yet examined the inflammation-associated pharmacological activity of Potentilla glabra Var. mandshurica (Maxim.) Hand.-Mazz ethanol extract (Pg-EE). To examine the mechanisms by which Pg-EE exerts anti-inflammatory effects, we studied its activities in lipopolysaccharide (LPS)-treated murine macrophage RAW264.7 cells and an HCl/EtOH-induced gastritis model. LPS-triggered nitric oxide (NO) release and mRNA levels of inducible nitric oxide synthase (iNOS), tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), and interleukin-1 beta (IL-1β) in RAW264.7 cells were suppressed by Pg-EE in a dose-dependent manner. Using a luciferase assay and western blot assay, we found that the NF-κB pathway was inhibited by Pg-EE, particularly by the decreased level of phosphorylated proteins of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) subunits (p65 and p50), inhibitor of kappa B alpha (IκBα), p85, and Src. Using an overexpression strategy, cellular thermal shift assay, and immunoprecipitation analysis, we determined that the anti-inflammatory effect of Pg-EE was mediated by the inhibition of Src. Pg-EE further showed anti-inflammatory effects in vivo in the HCl/EtOH-induced gastritis mouse model. In conclusion, Pg-EE exerts anti-inflammatory activities by targeting Src in the NF-κB pathway, and these results suggest that Pg-EE could be used as an anti-inflammatory herbal medicine.